Application of D-Limonene as the Green High Viscosity Friction Reducer in Hydraulic Fracturing - Aji, A.Q.M. (Unconventional Resources Technology Conference (URTEC), 2021)
High viscosity friction reducer (HVFR) has been used in the hydraulic fracturing fluid to reduce the frictional loss along the wellbore. The success of friction reducers has been demonstrated through research and industrial implementation. However, concerns regarding chemical usage provide the industry with the opportunity to review current chemistries. The main objective of this study is to investigate environmental-friendly hydraulic fracturing fluid additives. D-limonene, a surfactant from orange peel, will be introduced in hydraulic fracturing fluid as one of the additives (HVFR). This study uses two different surfactants: biodegradable surfactant from orange peel, also known as D-limonene, and the commercialized surfactant Alpha Olefin Sulfonate (AOS). Thermalgravimetric analysis (TGA) were conducted to determine the stability of surfactant before the analysis was conducted. TGA showed that D-limonene has a higher onset temperature at 380°C compared to the AOS with 280°C. Higher onset temperature indicates higher thermal stability to tolerate high reservoir temperature. The hydraulic fracturing fluids were formulated with 180,000 ppm brine following the salinity of the Montney formations, with the concentration of the surfactants varied from 0.2 - 1.0 wt.. The rheological analysis of hydraulic fracturing fluids was conducted at a temperature ranging from 25 - 70°C and at a constant shear rate of 40 sec-1. Flow loop tests were conducted to determine the performance of formulated hydraulic fracturing fluids. The tests were conducted at ambient conditions at a flow rate of 0.09 m3/min. Primarily, the addition of D-limonene in formulated hydraulic fracturing fluids increased the viscosity of the fluid. Addition of 0.4 wt. D-limonene showed an improvement of viscosity to 1.2 cP. Meanwhile, the addition of 1.0 wt AOS reduced the apparent viscosity of the hydraulic fluid to 0.56 cP. Higher viscosity is crucial to ease the flow of the hydraulic fracturing fluid to create the fractures and bring the proppant into the fractures created. The flow loop test showed that the hydraulic fracturing fluid with D-limonene reduced 50 of friction within the wellbore. The D-limonene reached hydration time 90 seconds faster than AOS. A shorter hydration time indicates the effectiveness of D-limonene as the HVFR. © 2021 Unconventional Resources Technology Conference (URTeC)